Power Rivalry in the Post-Soviet Space in Political and Military Domain - Włodkowska-Bagan, Agata (The Copernicus Journal of Political Studies, 2018)
Since the mid-90s the Russian Federation has remained the most important player in the CIS region. It has the greatest potential of instruments which can be used towards the post-Soviet states in political and military domain to maintain and maybe even broaden its influence in its former colonies. It seems that Iran has the least potential to employ. Its situation is the most complex one because of Western and Turkish concerns not only about fundamentalism export to the Muslim post-Soviet countries but also the disturbing issues not directly connected with the CIS region – Iranian nuclear program, its backing for terrorist organization in the Middle East, its anti-Israeli position and Teheran engagement in the Syrian conflict. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762